Carboxylated N-glycans on RAGE promote S100A12 binding and signaling - Srikrishna, Geetha (2010)
RAGE, the Receptor for Advanced Glycation End Products, is a signaling receptor protein of the immunoglobulin superfamily implicated in multiple pathologies. It binds a diverse repertoire of ligands, but the structural basis for the interaction of different ligands is not well understood. We earlier showed that carboxylated glycans on the V-domain of RAGE promote the binding of HMGB1 and S100A8/A9. Here we study the role of these glycans on the binding and intracellular signaling mediated by another RAGE ligand, S100A12. S100A12 binds carboxylated glycans, and a subpopulation of RAGE enriched for carboxylated glycans shows more than ten fold higher binding potential for S100A12 than total RAGE. When expressed in mammalian cells, RAGE is modified by complex glycans predominantly at the first glycosylation site (N25IT) that retains S100A12 binding. Glycosylation of RAGE and maximum binding sites for S100A12 on RAGE are also cell type dependent. Carboxylated glycan-enriched population of RAGE forms higher order multimeric complexes with S100A12, and this ability to multimerize is reduced upon deglycosylation or by using non-glycosylated sRAGE expressed in E.coli. mAbGB3.1, an antibody against carboxylated glycans, blocks S100A12 mediated NF-κB signaling in HeLa cells expressing full length RAGE. These results demonstrate that carboxylated N-glycans on RAGE enhance binding potential and promote receptor clustering and subsequent signaling events following oligomeric S100A12 binding.